Malaria parasitaemia and mRDT diagnostic performances among symptomatic individuals in selected health care facilities across Ghana - Benjamin Abuaku; Linda Eva Amoah; Nana Yaw Peprah; Alexander Asamoah; Eunice Obeng Amoako; Dickson Donu; George Asumah Adu; Keziah Laurencia Malm (BMC, 2021)
Abstract Background Parasitological diagnosis generates data to assist malaria-endemic countries determine their status within the malaria elimination continuum and also inform the deployment of proven interventions to yield maximum impact. This study determined prevalence of malaria parasitaemia and mRDT performances among febrile patients in selected health care facilities across Ghana. Methods This study was a cross-sectional survey conducted in the previously 10 regions of Ghana from May to August 2018. Each patient suspected to have uncomplicated malaria was tested using microscopy and two malaria rapid diagnostic tests (mRDTs): routinely used CareStart™ Malaria HRP2 (Pf) and SD Bioline Malaria Ag Pf (HRP2/pLDH). Main outcome variables were malaria slide and CareStart™ Malaria HRP2 (Pf) positivity rates; and diagnostic accuracy of CareStart™ Malaria HRP2 (Pf) and SD Bioline Malaria Ag Pf (HRP2/pLDH) using microscopy as "gold standard". Results Overall parasite positivity rates were 32.3% (6266/19402) by mRDT and 16.0% (2984/18616) by microscopy, with Plasmodium falciparum mono-infection accounting for 98.0% of all infections. The odds of parasitaemia by microscopy was significantly lower among female patients compared with males (OR = 0.78; 95% CI: 0.66-0.91), and among patients with history of previous antimalarial intake compared with those with no such history (OR = 0.72; 95% CI: 0.54-0.95). Overall sensitivity of CareStart™ Malaria HRP2 (Pf) was statistically similar to that of the HRP2 band of SD Bioline Malaria Ag Pf (HRP2/pLDH) combo kit (95.4%; 95% CI: 94.6-96.1 vs 94.3%; 95% CI: 93.4-95.1; p = 0.065) but significantly higher than the pLDH band (89.3%; 95% CI: 88.1-90.4; p < 0.001). The same pattern was observed for negative predictive value. Conclusions Malaria control interventions should be targeted at the general population, and history of antimalarial intake considered a key predictor of malaria slide negativity. Furthermore, HRP2-based mRDTs remain effective diagnostic tool in the management of suspected uncomplicated malaria in the country.